Roles of DICER-LIKE and ARGONAUTE Proteins in TAS-Derived Small Interfering RNA-Triggered DNA Methylation - Wu, Liang; Mao, Long; Qi, Yijun (Plant physiology (Bethesda), 2012)
Trans-acting small interfering RNAs (ta-siRNAs; TAS) emerge as a class of plant-specific small RNAs that are initiated from microRNA-mediated cleavage of TAS gene transcripts. It has been revealed that ta-siRNAs are generated by the sequential activities of SUPPRESSOR OF GENE SILENCING3 (SGS3), RNA-DEPENDENT RNA POLYMERASE6 (RDR6), and DICERLIKE4 (DCL4), and loaded into ARGONAUTE1 (AGO1) proteins to posttranscriptionally regulate several target genes by messenger RNA cleavage in trans. Here, we showed a high cytosine DNA methylation status at ta-siRNA-generating loci in Arabidopsis (Arabidopsis thaliana), which is dependent on RDR6, SGS3, and DNA-DIRECTED RNA POLYMERASE V (PoIV). More important, we found that DCL1 is the only DCL protein that is required for TAS3 loci DNA methylation, and all four DCLs exert combinatory functions in the methylation of TASI loci, suggesting a previously unknown role for DCL1 in directly processing TAS gene transcripts. Furthermore, we demonstrated that AGO4/6 complexes rather than AGO1 are responsible for TAS siRNA-guided DNA methylation. Based upon these findings, we propose a novel ta-siRNA pathway that acts at both the messenger RNA and chromatin level.